Analysis of internal wave in the Buru Island coastal waters, Banda Sea, Indonesia - Asmoro N.W.; Pranowo W.S.; Nurhidayat (Kuwait Journal of Science)
The Indonesian throughflow (ITF) in the eastern part of Indonesia passes through the Maluku, Taliabu, Sula, and Buru Islands to the Banda Sea. The average depth of the Buru and Sula Islands is between 1000 m and 5000 m, with a narrow gap (sill) located to the north and south at a depth of 165 m on the sea map. This topography makes for interesting research on the western waters of Buru Island. Therefore, this study aimed to obtain salinity, temperature, and density values as water column stratification associated with the internal wave (IW), thermocline area, and current patterns at specific depths in the waters of Buru Island, Banda Sea. Data were collected from initial observations of Sentinel 1 satellite imagery of Buru Island to obtain an image of the waves in the water area. Furthermore, a single beam echosounder (SBES), conductivity temperature depth (CTD), and Copernicus Marine were analysed at the same position and time. The research found a non-linear IW Mode 2 at depths of 440–540 m with an estimated amplitude length is 40 km and an amplitude height of 100 m. Based on SBES echogram imaging, CTD data analysis, and modelling, there was an increase in IW density, a 35.25 PSU increase in salinity value at depths of 50∼200 m, a temperature decrease of 27.5 °C to 10 °C at depths of 50∼300 m, and a density stratification of 23.5 kg/m³ to 27 kg/m³ at depths of 50∼300 m. © 2024